“Kepala Putik” on Women: Perspectives and Challenges in Balancing the Dual Role as Mother and Worker in Indonesia - Primadona, Fitry; Lenggogeni, Sari (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2024)
The dual roles carried out by Indonesian women as both mothers and workers have increasingly garnered attention amidst dynamic social and economic changes. This article explores the concept of